Evaluating permanent deformation in asphalt rubber mixtures - Fontes, Liseane P. T. L. (2009)
Permanent deformation or rutting, one of the most important distresses inflexible pavements, has long been a problem in asphalt mixtures. Throughout the years, researchers have used different test methods lo estimate the performance of asphalt mixtures in relation to rutting. One of the alternatives to reduce permanent deformation in asphalt pavement layers is through the use of mixtures produced with asphalt rubber This work aims at comparing the performance of a conventional dense graded mixture and that of asphalt rubber mixtures (dense and gap graded) in what respects to rutting. The asphalt rubber mixtures were produced by the wet process (continuous blend at laboratoty and tire rubber-modified asphalt binder at an industrial plant). To study their performance, two laboratory tests, the Repeated Simple Shear Test at Constant Height RSST-CH,) and the Accelerated Pavement Testing Simulator test (wheel tracking) were carried out. The results from this study showed that asphalt rubber mixtures can be an alternative to minimize permanent deformation in asphalt pavement layers and that the resilience of asphalt rubber binders can be an indicator off that performance.